Numerical Study of a Buckling Restrained Brace (BRB) in Steel Structures and Comparison with a Convergent Ordinary Brace (OCB) Under Static and Dynamic Loading - Habibpour, Fatemeh (UI Scholars Hub, 2021)
Bulk metallic glass (BMG) has good mechanical strength, high hardness, wear resistance, and corrosion resistance with promising application in various industries. However, for the industrial production of BMG, the main issue is how to overcome limitations of joining with other materials. The present study focuses on solder processing at low operating temperature to avoid exceeding the recrystallization temperature. A feasible joining process for BMG was developed using lead-free solders. The BMG surface is pre-plated with copper, nickel, or titanium as a wetting layer. The reaction temperature is set between the glass transition temperature of BMG and the melting point of the solder. After a reflowing and aging process, the joint sample was examined using SEM, EDS, EPMA, and XRD. The Cu–Zr based BMG can be successfully joined with Sn-58Bi solder after plating Cu on the BMG surface. A diffusion layer was observed and the thickness increased with longer aging time. The main components of the diffusion layer are ZrO2 and Cu10Zr7.